Evolução de encosta em contexto de paleocabeceira de drenagem da bacia do rio Capão Grande no quaternário tardio -superfície de Pinhão/Guarapuava - Biffi, Vitor Hugo Rosa (2019)
The present work had as objective to verify the evolution of slope in the context of paleovalley head of the of Pinhão/Guarapuava geomorphic summit surface, through the systematic description of the superficial formations by lito-, pedo-, alo-, and chronostratigraphy criteria. In order to reach the objective, a stratigraphic section was described in section of road in said surface, and together with laboratory analyzes (granulometry, mineralogical analysis, micromorphology, magnetic susceptibility by mass unit, carbon isotope composition and absolute dating) were establish the processes in the evolution of slope in paleovalley head, and its relation with the phenomena of morphogenesis and pedogenesis in the Late Quaternary. The results allowed to recognize, from the base to the top, a buried paleosol level, three coluvial sequences and a co-alluvial sequence. The pedostratigraphic description indicated the presence of nine stratigraphic horizons, whose evolution is due to the dynamics between pedogenesis and morphogenesis that occurred during Late Pleistocene and Holocene. The mineralogical analysis showed that the polygenetic surface formations in high stage of weathering, due to the processes of fersialitization. The data obtained by the micromorphological description suggest the performance of runoff and mass movement in the reworking of materials along the slope. These phenomena were correlated to the researchs of Palmas/Caçador Summit Surface, seeking to establish regional paleoenvironmental correlations. The ages obtained via 14C and LOE suggest that the morphogenesis acted from the Late Glacial Maximum to the Holocene, provoking the formation of colluvial and co-aluvios deposits by Earth Flow and hyperconcentrated flow. In the middle Holocene is recorded the occurrence linear erosive incision (gully), whose sedimentation dates to the Late Holocene. Progressive pedogenesis acted mainly in MIS 3, and among sedimentation episodes of colluvial units. Together, the performance of the morphogenesis and pedogenesis caused partial inversion of the relief, due to erosion of the side slope materials and sedimentation in the medium / low slope.